2010
DOI: 10.1249/mss.0b013e3181c5b8a8
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Extravascular Lung Water and Cardiac Function in Trimix SCUBA Diving

Abstract: This is the first report that asymptomatic SCUBA dives are associated with accumulation of EVLW with concomitant increase in PAP, diminished left ventricular contractility, and increased release of NT-proBNP, suggesting a significant cardiopulmonary strain. EVLW and PAP did not return to baseline during repetitive dives, indicating possible cumulative effect with increasing the risk for pulmonary edema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 32 publications
2
28
1
Order By: Relevance
“…Even in the absence of DCS, SCUBA diving is associated with a number of asymptomatic changes that can be detected following a dive. They include generation of silent bubbles and alterations in cardiovascular function, i.e., decrease in ventricular contractility, increase in pulmonary arterial pressure, increased secretion of atrial natriuretic peptide and endothelial dysfunction; and pulmonary function, i.e., change in lung diVusing properties, reduction in spirometric parameters and accumulation of extravascular lung water (Dujic et al 2006;Marabotti et al 1999;Marinovic et al 2009Marinovic et al , 2010Obad et al 2007a).…”
Section: Introductionmentioning
confidence: 99%
“…Even in the absence of DCS, SCUBA diving is associated with a number of asymptomatic changes that can be detected following a dive. They include generation of silent bubbles and alterations in cardiovascular function, i.e., decrease in ventricular contractility, increase in pulmonary arterial pressure, increased secretion of atrial natriuretic peptide and endothelial dysfunction; and pulmonary function, i.e., change in lung diVusing properties, reduction in spirometric parameters and accumulation of extravascular lung water (Dujic et al 2006;Marabotti et al 1999;Marinovic et al 2009Marinovic et al , 2010Obad et al 2007a).…”
Section: Introductionmentioning
confidence: 99%
“…; Marinovic et al. ). Indeed, the effects of increased central venous pressure may augment PFO recruitment created by breathing against resistance.…”
Section: Discussionmentioning
confidence: 97%
“…; Marinovic et al. ). Increases in left ventricular and atrial pressures may create a left‐to‐right atrial pressure gradient that would oppose right‐to‐left flow through the PFO.…”
Section: Discussionmentioning
confidence: 97%
“…However, a recent study has shown that even presumably safe dives with few VGE and no DCI symptoms were associated with significant cardiac strain and increased levels of BNP (Marinovic et al. ). Grassi et al.…”
Section: Discussionmentioning
confidence: 99%